2022
DOI: 10.2478/aiht-2022-73-3621
|View full text |Cite
|
Sign up to set email alerts
|

Light and heavy ferritin chain expression in the liver and kidneys of Wistar rats: aging, sex differences, and impact of gonadectomy

Abstract: Ferritin is the main intracellular storage of iron. Animal studies show that female liver and kidney express more ferritin and accumulate more iron than male. However, no study so far has investigated sex and age differences in light (FtL) and heavy (FtH) ferritin chain expression. To address this, we relied on specific antibodies and immunochemical methods to analyse the expression of both ferritin chains in the liver and kidney of 3-month and 2-year-old male and female Wistar rats. To see how sex hormones ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…We have recently shown that iron-loaded hepatocytes undergo ferroptosis because of iron-catalyzed overproduction of mitochondrial reactive oxygen species (mtROS) [ 32 ]. Intriguingly, sexual dimorphism in iron metabolism has been well noted in humans and in experimental rodents [ [33] , [34] , [35] ]. Hepatocytes, which compromise approximately 80% of the liver mass, play an important role in systemic iron homeostasis via the deposition of excessive body iron and production of hepcidin [ 36 ], a master regulator of iron metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that iron-loaded hepatocytes undergo ferroptosis because of iron-catalyzed overproduction of mitochondrial reactive oxygen species (mtROS) [ 32 ]. Intriguingly, sexual dimorphism in iron metabolism has been well noted in humans and in experimental rodents [ [33] , [34] , [35] ]. Hepatocytes, which compromise approximately 80% of the liver mass, play an important role in systemic iron homeostasis via the deposition of excessive body iron and production of hepcidin [ 36 ], a master regulator of iron metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that iron-loaded hepatocytes undergo ferroptosis because of iron-catalyzed overproduction of mitochondrial reactive oxygen species (mtROS) [18]. Intriguingly, sexual dimorphism in iron metabolism has been well noted in humans and in experimental rodents [19][20][21]. Hepatocytes, which compromise approximately 80% of the liver mass, play an important role in systemic iron homeostasis via the deposition of excessive body iron and production of hepcidin [22], a master regulator of iron metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, one study showed sex-specific association between brain iron content and cognitive decline in aging-related iron disturbance (32). In a study of healthy individuals (93 males and 72 females), there was a significant increase in brain ferritin iron in the basal ganglia and hippocampus associated with aging, however women showed much lower brain ferritin than men (33). Interestingly, the kidney and liver of aging female rats showed higher expression of ferritin than in males (34).…”
Section: Introductionmentioning
confidence: 99%